HPLC and anti-inflammatory studies of the flavonoid rich chloroform extract fraction of Orthosiphon stamineus leaves. - Yam, Mun Fee; Lim, Vuanghao; Muhammad Salman, Ibrahim; Ameer, Omar Ziad; Ang, Lee Fung; Noersal , Rosidah; Abdulkarim, Muthanna Fawzy; Abdullah, Ghassan Zuhair; Basir, Rusliza; Sadikun, Amirin; Asmawil, Mohd Zaini (MDPI, 2010)
The aim of the present study was to verify the anti-inflammatory activity of Orthosiphon stamineus leaf extracts and to identify the active compound(s) contributing to its anti-inflammatory activity using a developed HPLC method. Active chloroform extract of O. stamineus was fractionated into three fractions using a dry flash column chromatography method. These three fractions were investigated for anti-peritoneal capillary permeability, in vitro nitric oxide scavenging activity, anti-inflammatory and nitric oxide (NO) inhibition using carrageenan-induced hind paw edema method. The flavonoid rich chloroform extract fraction (CF2) [containing sinensetin (2.86% w/w), eupatorin (5.05% w/w) and 3'-hydroxy-5,6,7,4'-tetramethoxyflavone (1.101% w/w)], significantly reduced rat hind paw edema, NO and decreased dye leakage to peritoneal cavity at p < 0.05. IC50 of in vitro NO scavenging of CF2 was 0.3 mg/mL. These results suggest that the anti-inflammatory properties of these CF2 may possibly be due to the presence of flavonoid compounds capable of affecting the NO pathway.